Adsorptive Desulfurization of Liquid Fuels Using Na-Bentonite Adsorbents - Ali, Fatma Dheif (Al-Nahrain Journal for Engineering Sciences, 2018)
In this work, model fuel (Thiophene in hexane) was treated for sulfur removal by adsorptive desulfurization method using modified bentonite with sodium (Na-B) adsorbent. Batch and continuous mode were used in this study. Several operating parameters such as initial thiophene concentration of 250 to 2000 mg/L , adsorbent dose 0.1 to 0.8g/ml were studied for sulfur removal %. Also a comparison between raw and modified bentonite was performed in this study. In continuous mode, a packed bed of Na-B adsorbent column was used at constant initial thiophene concentration and liquid hourly space velocity (LHSV) to study the breakthrough curve of thiophene. The results showed that Na-B adsorbent was better than raw bentonite in removal of sulfur components. The removal percentages was 67,75,87,and 91% for 500 mg/L initial thiophene concentration using adsorbent dose o.1, 0.2, 0.4 and 0.8g/ml respectively , and 87, 75, 57, and 53% for adsorbent dose of 0.2 g/ml using initial thiophene concentration of 250, 500, 1000, and 2000 mg/L respectively. It was concluded that when increase the dose of adsorbent, the removal of sulfur increase , and when increase the initial concentration the removal decrease.